INVESTIGATION OF IMPROVED CHROMAMETRY MEASUREMENT ALGORITHM FOR PALM OIL FRESHNESS & SAFETY IDENTIFICATION USING MOBILE PHONE - ABDUL RAZAK, FARAH NABILLAH (2017)
The main objective of this project is to develop a user-friendly apps that will measure the freshness of food based on Chromametry Measurement. This apps is targeted for consumer to perform in-site check on the freshness of the food before buying the product. This app is also for the retailer that obtain the product from the supplier ensure that the product is still fresh even before reaching the expiry date and also for the evaluator to evaluate the product. The main criteria in developing the apps is by understanding the concept of colour in food industry. The l*a*b colour space is used to compare to others colour space which is RGB to improve the measurement. The b parameter which is the sensitivity of the mobile phone was also been investigated to reduce the colour error calculation. The relationship between the colour space and the chromametry algorithm measurement is the core thing in this project because this criteria will determine whether the food is fresh or not. . The l*a*b colour space also being compared with the RGB colour space to evaluate which colour space gave a linear result to calculate the error calculation. The relationship between colour space and the chromametry algorithm measurement is the main criteria when determining the freshness of the food.